Ecological transition: from the end-of-pipe to ecosystem approach for waste management in Malaysian City - Ahmad Fariz Mohamed,; Abdul Samad Hadi,; Shaharudin Idrus ,; Abdul Hadi Harman Shah, (Universiti Kebangsaan Malaysia, 2011)
Cities in Malaysia are experiencing rapid changes of their natural ecosystem. The development process of cities has transformed natural ecosystem into many types of land use in accordance with human development needs. As population grows and urban expands, waste and economic activities have also continued significantly over the decades. Since Malaysia’s independence in 1957, waste has been managed through the end-of-pipe approach which focuses on disposals of wastes to landfill. This practice gives negative impact to the environment and human health. Moreover, this approach increases costs to wastes generator and more landfills are required. The ecosystem functions are affected, and land value will decline there in the future. Being aware of these problems, cities in Malaysia have embarked on many programs in managing wastes in a sustainable manner. One of the activities is through recovery of waste as resources and these include recycling, reuse and reduce or 3R approaches. Since 1980s waste minimisation and the use of cleaner technology have been introduced. Therefore, the need for efficient urban ecosystem in managing resources consumption and waste generation is very important. A framework is needed within which to improve knowledge and decision making about materials used, waste reduction and pollution prevention. This framework will include systems that promote waste minimisation, waste recovery, waste exchange and conservation. Ultimately using natural ecosystem approach for cities to manage its wastes will ensure that it will be able to maintain its ecosystem functions and services for sustainable development